Pangasinan, Pinablin Dalin history, culture, development [Book review] - Fernandez, Erwin S. (2016)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/5499/4933
Keywords: Books -- Reviews; Pangasinan Historical and Cultural Commission (PHCC); Urduja, Princess